Re: Ashley M. Hopkins, Ganessan Kichenadasse, Christos S. Karapetis, et al. Concomitant Proton Pump Inhibitor Use and Survival in Urothelial Carcinoma Treated with Atezolizumab. Clin Cancer Res. In press. https://doi.org/10.1158/1078-0432.CCR-20-1876 - Satoshi Funada; Takashi Yoshioka; Yan Luo (European Urology Oncology, 2020)
Introduction Homozygous deletion of 9p21, containing CDKN2A/B and MTAP (CMdel), underlies emerging therapeutic strategies including PRMT5/MAT2A inhibition. The clinicogenomic context and treatment outcomes of CMdel in NSCLC remain incompletely defined. Methods We analyzed Tempus Lens records with paired DNA/RNA sequencing. After quality filtering, 16,947 patients were included in the primary dataset and 10,996 in the validation dataset, and stratified by deletion status (CMdel vs CMwt). Interferon status was defined by interferon-kappa (IFNK) expression (log2[TPM+1]) using the 25th percentile of CMwt as threshold. Immune composition was inferred by quanTIseq. First-line regimens were grouped as ICI-mono, ICI-chemo, chemotherapy, or TKI. Best response and time-to-next-treatment with risk-set adjustment were assessed. Results CMdel occurred in 11.7% (n=1,991) and 15% (n=1,676), and was enriched in mucinous histology, stage IV disease, and never-smokers. CMdel associated with EGFR, TERT, and SMARCA4 alterations, whereas CMwt associated with RB1, SETD2 and ARID2. >50% of CMdel tumors harbored targetable co-alterations, enriched in EGFR/ALK/RET and relatively depleted in KRAS. CMdel tumors exhibited lower PD-L1, mutation burden, and immune infiltration. TTNT did not differ by CM status for ICI-mono or TKI, but was shorter in CMdel for ICI-chemo and chemotherapy. Discordant and broad deletions were less common and had weaker TTNT association. IFNK-low expression marked immune-excluded subgroups with worse treatment outcomes. Conclusions CDKN2A/MTAP loss defines a prevalent, genomically distinct NSCLC subset enriched in actionable drivers. CMdel associates with worse outcomes to ICI/chemotherapy-containing regimens. These findings highlight convergent biology at 9p21 and support biomarker-guided development of PRMT5/MAT2A inhibitors in MTAP-deleted NSCLC.